The role of microtransactions in impulse buying and purchase intention in the video game market - Rita, P. (2024)
Despite having great potential, microtransactions are an understudied business model in the video game industry. The current study explores the buying process of microtransactions to highlight the most important factors affecting such behavior. Using pre-validated scales, a questionnaire was administered online to 301 participants who were asked to evaluate their impulse buying tendency (IBT) and purchase intention (PI) for microtransactions within gaming scenarios. The study found a positive relationship between drivers, such as performance, hedonic content and social factors, flow experience, and impulse buying. This tendency leads to a higher intention to purchase microtransactions. Businesses can utilize the paper’s findings to tailor their microtransaction content to these drivers, leading to higher profits.